KONSEP PEMBELAJARAN PIANO: SEBUAH SUMBANGSIH PEMIKIRAN - Genta Kurnia Andriyanto (Sekolah Tinggi Theologia Abdiel, 2018)
Practicing a piano is important for a pianist. A good training program certainly needs to be designed for every pianist. Long time and self-discipline as the basis for training, is actually not enough to get maximum results. Complaints such as saturation, boredom, finger injury, even frustration are always a cliché problem that often occurs. Creating a training program that is right on target and efficient is very necessary to be designed, so that training can be fun, stimulate and of course get a fast and significant development. Then what kind of exercise program should the pianist know in order to get maximum results? The following will explain some of the suggestions and trick that can help a pianist, so he can make the best use of training time.